MicrobioSee: A Web-Based Visualization Toolkit for Multi-Omics of Microbiology - Li, JinHui; Sang, Yimeng; Zeng, Sen; Mo, Shuming; Zhang, Zufan; He, Sheng; Li, Xinying; Su, Guijiao; Liao, Jianping; Jiang, Chengjian (Frontiers in Genetics, 2022)
With the upgrade and development of high-throughput sequencing technology, multi-omics data can be obtained at a low cost. However, mapping tools that existed for microbial multi-omics data analysis cannot satisfy the needs of data description and result in high learning costs, complex dependent environments, and high fees for researchers in experimental biology fields. Therefore, developing a toolkit for multi-omics data is critical for microbiologists to save effort. In this work, we developed MicrobioSee, a real-time interactive visualization tool based on web technologies, which could visualize microbial multi-omics data. It includes seventeen modules surrounding the major omics of microorganisms such as transcriptome, metagenome, and proteome. With MicrobioSee, methods for plotting are simplified in multi-comics studies, such as visualization of diversity, ROC, and enrichment pathways for DEGs. Subsequently, three case studies were chosen to represent the functional application of MicrobioSee. Overall, we provided a concise toolkit along with user-friendly, time-saving, cross-platform, and source-opening for researchers especially microbiologists without coding experience. MicrobioSee is freely available at https://microbiosee.gxu.edu.cn.